Hydrogen sulphide alleviates iron deficiency by promoting iron availability and plant hormone levels in Glycine max seedlings - Chen, Juan; Zhang, Ni-Na; Pan, Qing; Lin, Xue-Yuan; Shangguan, Zhouping; Zhang, Jian-Hua; Wei, Ge-Hong (BMC plant biology, 2020)
Background Hydrogen sulphide (H 2 S) is involved in regulating physiological processes in plants. We investigated how H 2 S ameliorates iron (Fe) deficiency in soybean ( Glycine max L.) seedlings. Multidisciplinary approaches including physiological, biochemical and molecular, and transcriptome methods were used to investigate the H 2 S role in regulating Fe availability in soybean seedlings. Results Our results showed that H 2 S completely prevented leaf interveinal chlorosis and caused an increase in soybean seedling biomass under Fe deficiency conditions. Moreover, H 2 S decreased the amount of root-bound apoplastic Fe and increased the Fe content in leaves and roots by regulating the ferric-chelate reductase (FCR) activities and Fe homeostasis- and sulphur metabolism-related gene expression levels, thereby promoting photosynthesis in soybean seedlings. In addition, H 2 S changed the plant hormone concentrations by modulating plant hormone-related gene expression abundances in soybean seedlings grown in Fe-deficient solution. Furthermore, organic acid biosynthesis and related genes expression also played a vital role in modulating the H 2 S-mediated alleviation of Fe deficiency in soybean seedlings. Conclusion Our results indicated that Fe deficiency was alleviated by H 2 S through enhancement of Fe acquisition and assimilation, thereby regulating plant hormones and organic acid synthesis in plants.